Impact of Climate Change on Gujjar and Bakarwal Communities of Jammu and Kashmir - Mir, Sajad Ahmad; Batool, Maliha (Journal of Sustainability and Environmental Management, 2022)
Climate change is a global issue that affects everyone. It has been estimated that the developing nations will suffer the most from the effects of climate change. The underdeveloped nations will most likely experience the negative effects of climate variability. They are more susceptible to climate change due to their low adaptive capacity. This study has found the impact of climate change on the Gujjar and Bajarwals of Jammu and Kashmir. The present study is based on the primary data collected from 507 respondents of Thanala village of Bhaderah tehsil of Doda district of Jammu and Kashmir. The data was collected using survey questionnaire and was analysed through various statistical tools to draw results. The pastoralist community is one of the many communities that were most vulnerable to the effects of climate change. Modernization was identified as the major cause behind climatic changes. Climate change and the livelihood patterns of pastoralists are interlinked with each other. This relationship is not only linked to the traditional adaptation strategies but also to the level of land-use change.